Draw 50 animal 'toons : the step-by-step way to draw dogs, cats, birds, fish, and many, many more-- - Ames, Lee J. (Ames, Lee J. Draw 50 (Watson-Guptill Publications), 2012)
Offer step-by-step illustrated instructions for drawing a variety of animals, from fish to lions.